Enhancing growth of buckwheat sprouts and microgreens by endophytic bacterium inoculation - Xoxiong Briatia (2018)
© 2017 Friends Science Publishers. This study evaluated the effect of endophytic bacterium inoculation on sprouts and microgreens growth of common buckwheat. The endophtyic bacterium isolate ST-B2, isolated from common buckwheat seedling stems was identified to be Herbaspirillum sp. based on analysis of partial nucleotide sequence 16S rRNA gene. Inoculation of bacterial strain ST-B2 markedly enhanced the growth of common buckwheat sprouts and microgreens. The highest effect of seed inoculation with bacterial endophyte on sprouts growth was found in treatment of 20% (v/v) inoculum (2.0×10-7cfu.mL-1) while 10% (v/v) inoculum (1.0×10-7cfu.mL-1) had the highest effect on growth of microgreens. Inoculated sprouts growth at 25°C and 30°C showed the longer hypocotyl length and higher sprouts yield than at 20°C. Microgreens growth, fresh and dry weights increase was dependent on inoculation concentrations and days of microgreens grew. Seed inoculation and soil inoculation also exhibited the enhancing effects on microgreens growth, fresh and dry weight. The positive effects of seed and soil inoculation of Herbaspirillum sp. ST-B2 on sprouts and microgreens growth indicate the feasibility to increase the production yield of common buckwheat species.